BODIPY Dyes Bearing Multibranched Fluorinated Chains: Synthesis, Structural, and Spectroscopic Studies. Issue 38 (11th June 2019) - Martinez Espinoza, Maria I.; Sori, Lorenzo; Pizzi, Andrea; Terraneo, Giancarlo; Moggio, Ivana; Arias, Eduardo; Pozzi, Gianluca; Orlandi, Simonetta; Dichiarante, Valentina; Metrangolo, Pierangelo; Cavazzini, Marco; Baldelli Bombelli, Francesca
Abstract: A small series of boron‐dipyrromethene (BODIPY) dyes, characterized by the presence of multibranched fluorinated residues, were designed and synthesized. The dyes differ in both the position ( para ‐perfluoroalkoxy‐substituted phenyl ring or boron functionalization) and number of magnetically equivalent fluorine atoms (27 or 54 fluorine atoms per molecule). Photophysical and crystallographic characterization of the synthesized BODIPYs was carried out to evaluate the effect of the presence of highly fluorinated moieties on the optical and morphological properties of such compounds. Abstract : Branching out : Four multibranched fluorinated boron‐dipyrromethene (BODIPY) dyes have been designed and prepared (see figure). Photophysical and crystallographic characterization of these BODIPYs was carried out to evaluate the effect of the presence of fluorinated moieties on the optical and morphological properties.